Dynamics of alfalfa production in Hungary: Changes in harvested area, yield, and total production over 30 years (1990 – 2024) - Appiah, Ebenezer Ayew; Kuunya, Ronald; Kutasy, Erika Tünde (Acta Agraria Debreceniensis, 2025)
Alfalfa is a crucial forage crop in Hungary, contributing to sustaining livestock feed and soil fertility management. To assess the dynamics of alfalfa crop production in the country, this study examines the variations and patterns in harvested area, total production, arable land area, and average yield of alfalfa over the previous three decades (1990 to 2024). Our findings reveal fluctuating patterns, with periods of increase and decrease in all parameters under study. While certain years exhibit growth due to favourable climatic conditions and improved agricultural practices, others show declines, potentially influenced by economic factors, changes in crop demand due to a decline in livestock production, and unfavourable climatic conditions, particularly drought. The analysis highlights the complication of alfalfa production trends, underscoring the need for expanding land area and adaptive strategies in Hungarian forage crop management to enhance alfalfa crop production to sustain livestock’s feeding system.